80-GHz RoF Based on Push–Pull Modulator - F. Zhao; J. L. Li; J. M. Gong; J. R. Bai; S. Y. Liang; Z. Q. Hui; D. D. Han; B. Liu; X. J. Xin (IEEE Photonics Journal, 2019)
A novel push-pull modulator based scheme to generate W-band millimeter-wave (mm-wave) vector signal was proposed and experimentally demonstrated. Related to an I/Q modulator, push-pull modulator has the advantages of simple architecture, small insertion loss and low cost. Through combining one 40 GHz upper sideband (USB) using a quadrature-phase-shift-keying (QPSK) modulation with a −40 GHz unmodulated lower sideband (LSB), a QPSK modulated 4 G-Baud 80 GHz single sideband vector mm-wave signal was successfully generated.